PEMBELAJARAN TAHSIN TILAWAH AL-QUR’A>N UNTUK PEMBACA PEMULA - Baktiar Leu (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2020)
It cannot be denied that the verses of the Quran are arranged with Arabic vocabulary. Except for a few words that entered the treasury duw tho acculturation. The Quran recognizes this in its many verses, including those that refute the accusation that the Quran was recommended by ‘Ajam (non-Arab) to the Prophet Allah. Arabic grammar is also very rational and Indonesian but it is quite complicated, especially when compared to. Al-Qur’an as a guide life for every Muslim. As a guide, of course we must always read it and understand its contents. In order to read properly and correctly according to the rules of recitation, it is necessary for us to study the Qur’an, especially learning how to read it. Through this Qur’an recitations we are trying to improve and smooth the reading of the Qur’an. Because reading and reciting letters of the Qur’an properly and correctly they are Muslims. Therefore, the writer of study about how Learning to Resist the Recitations of the Quran, for beginners Readers (Learning of the Quran, Good and Islamic way of being able to read the Quran well and in accordance with the rules that want to express is what the people believe). The approach uses a qualitative approach with data collection techniques in the form of document studies. While the data analysis technique uses content analysis is analyzes the contents of reading material related to this research. The results of the study explained that the recitation of the recitations of the Qur’an is an activity that emphasizes more on the correction or improvement of the reading of the Qur’an including makhorijul letters, letter character, relationship between letters, mad (long and short in reciting verses) and waqaf (start reading and stop at reading) as well as terms in the Qur’an